1989
DOI: 10.1021/j100354a044
|View full text |Cite
|
Sign up to set email alerts
|

Molecular motion of benzene, n-hexane, and cyclohexane in potassium zeolite L studied by deuterium NMR

Abstract: seems rather difficult when M is the tungsten.The MoS2 final product has been characterized by both HREM and LRS. A correlation exists to indicate that the Raman lines characteristic of MoS2 are sensitive to their crystal size. Dehydration of a sample before sulfidation noticeably affects the size of the supported MoS2 slabs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 0 publications
8
28
0
1
Order By: Relevance
“…This suggests that the molecule sits close enough to the channel walls so that the aromatic 6‐rings can interact with the zeolite's counterions (K + ). Experimental results and calculations have shown that the preferred adsorption sites for benzene in zeolite L are the counterions located in the channel walls 3437. Such a position would result in a slight hindrance of these motions and an increase of the energy needed to activate them.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the molecule sits close enough to the channel walls so that the aromatic 6‐rings can interact with the zeolite's counterions (K + ). Experimental results and calculations have shown that the preferred adsorption sites for benzene in zeolite L are the counterions located in the channel walls 3437. Such a position would result in a slight hindrance of these motions and an increase of the energy needed to activate them.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) measurements of hydrocarbon mobility in zeolites show that the rates of conformational changes are significantly slower than in the bulk (64). Picosecond measurements of reorientation times support this, showing moderately slower relaxation times (by a factor of 3) when a polar molecule (nitroben-zene) adsorbs to porous glass (65).…”
Section: Other Probes Of Surface Dynamicsmentioning
confidence: 97%
“…These values are (g Q ) consistent with the results of Silbernagel et al (93.0 kHz). 13 The QCC value is approximately half of that in rigid state kHz). 16 Solid also shows the (QCC 0 \ 193 ^3 benzene-d 6 half value above 135 K. 16,17 The benzene ring undergoes a fast rotation around the axis, while the ring plane is C 6 Ðxed.…”
Section: Benzenementioning
confidence: 99%
“…The mutual exchange is restricted. In the case of benzene/silicalite, spectral simulation has been performed assuming the presence of three components, but without presenting the detailed results of the simulation.8 Silbernagel et al 13 have studied the molecular motions of benzene, n-hexane and cyclohexane in KL zeolite. They discussed the mode of motion from the line shape qualitatively, and estimated the activation energy of the motion for and n-hexane-from the temperature depen-benzene-d 6 d 14 dence of the spinÈlattice relaxation time, Since the time T 1 .…”
Section: Introductionmentioning
confidence: 99%